INCREASING STUDENT LEARNING OUTCOMES IN THE FIELD OF NATURAL SCIENCE STUDY THROUGH EXPERIMENTAL LEARNING MODEL IN CLASS VI SD NEGERI 004 KEPENUHAN HULU, KEC. KEPENUHAN HULU, KAB. ROKAN ACADEMIC YEAR 2019/2020 - Sugianto Sugianto (STKIP Rokania Pasir Pangaraian, 2021)
Natural Sciences is a branch of science that studies natural phenomena, so Natural Sciences is also taught to elementary school students to improve the quality of the nation's education. The quality of the nation's life is largely determined by the education factor. The role of education is very important to create a smart, peaceful, open and democratic life. Therefore, educational reform must always be carried out to improve the quality of national education (Nurhadi, 2003: 1). Given the importance of Natural Sciences, the effort that must be made is to improve the learning process carried out by teachers by offering a learning approach with learning concepts that encourage teachers to make connections between the material being taught and students' real world situations. It also encourages students to make connections between the knowledge they have and its application in their own lives. One way to do that is by applying the Experimental Learning Model. This Classroom Action Research was conducted in class VI of SD Negeri 004 Kecepatan Hulu, Kecepatan Hulu District, Rokan Hulu Regency. In the 2019/2020 academic year, there were 24 students consisting of 15 male students and 9 female students. The stages in action research are planning, implementation, observation, evaluation, and reflection. The results of teacher observations showed good improvements and changes from the first cycle of the first meeting to the second cycle of the second meeting, namely from 72, 77, 85 to 90. Student learning outcomes also increased from cycle I meeting I to cycle II meeting II, starting from 71, 73, 80 to 86. In learning the field of Natural Sciences, teachers are expected to use a scientific experimental learning model so that students can play an active role in the learning process. By looking at the learning outcomes, of course, it can be developed with a scientific experimental approach in other learning